2023
DOI: 10.17221/44/2022-swr
|View full text |Cite
|
Sign up to set email alerts
|

Reducing greenhouse gas emission by alternation of the upland crop rotation in the Mekong Delta, Vietnam

Abstract: Agricultural production is one of the main sources of anthropogenic greenhouse gas (GHG) emissions, contributing 50% and 60% of CH<sub>4</sub> and N<sub>2</sub>O emissions, respectively. This study evaluated the rice yield and components, the CH<sub>4</sub> and N<sub>2</sub>O emissions and the global warming potential between the triple rice (R-R-R) and sesame-rice rotation (S-R-R) systems in Can Tho city, Vietnam. The experiments were conducted in three cropping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Emission fluxes were determined from the slope through linear regression, the concentration of CH 4 or N 2 O against chamber closure time [13,30]. Then, the slope was converted to mass per unit area per unit time (mg m −2 h −1 ) through Equation ( 3) [3,29]:…”
Section: Calculation Of Ghg Emissionsmentioning
confidence: 99%
“…Emission fluxes were determined from the slope through linear regression, the concentration of CH 4 or N 2 O against chamber closure time [13,30]. Then, the slope was converted to mass per unit area per unit time (mg m −2 h −1 ) through Equation ( 3) [3,29]:…”
Section: Calculation Of Ghg Emissionsmentioning
confidence: 99%
“…In the agricultural systems, several management practices including crop monocultivation, fertilizer application, soil preparation, and various crop rotation systems such as triple rice or rice-upland crops have been found with significant impacts on the structure and diversity of microbial communities in the soil [8][9][10][11][12]. Recently, farmers in the Vietnamese Mekong Delta (VMD) region have converted the intensive rice cultivation system into the rice-upland crops rotation model due to the change in environmental conditions [13][14][15][16]. Previous studies reported that bacterial communities had been associated with the decomposition of rice straw residues in flooded rice soil microcosms [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%